Statistical mixture design investigation for extraction and quantitation of aporphine alkaloids from the leaves of Unonopsis duckei R.E. Fr. by HPLC–MS/MS. Issue 6 (24th April 2018) - Rocha, Pablo R. N.; de Freitas, Flávio A.; Angolini, Célio F. F.; Vasconcelos, Lucas‐Smith F.; da Silva, Alaíde L. B.; Costa, Emmanoel V.; da Silva, Felipe M. A.; Eberlin, Marcos N.; Bataglion, Giovana A.; Soares, Patrícia K.; Koolen, Hector H. F.
Abstract: Introduction: Alkaloids‐derived drugs are a billionaire world‐market and several phytochemical investigations aim the identification of new sources and/or structures. Thus, improving the way of extracting and methods to quantify them are of utmost importance. Objective: To quantify isoquinoline‐derived alkaloids in Unonopsis duckei R.E. Fr. through a new validated high‐performance liquid chromatography with tandem mass spectrometry (HPLC–MS/MS) method in combination with a statistical mixture design that aimed a proper direct extraction of these compounds from leaves. Methodology: Extracts were obtained with acetone, methanol, chloroform, and n ‐hexane in different combinations and proportions. Chemometrics were applied in order to compare peak areas, and therefore evaluate synergism and antagonism effects between the solvents. After selection of extraction solvent, the quantification was validated and applied in the best solvent combination to quantify the main alkaloids in U. duckei . Results: Chemometrics indicated a synergistic effect between chloroform and methanol solvents, thus improving alkaloid extraction and extract yield. Analytes were quantified in a 15‐min method, with limits of detection (LODs) between 0.5 and 5.2 ng/mL and limits of quantification (LOQs) between 1.6 and 17.2 ng/mL. The accuracy ranged between 80 and 120%. Coefficients of variation were lower than 17.42% at all concentrations. Concentrations of the alkaloids in U. duckei varied from 6.79 to 131.10 μg/g of dried leaf and glaziovine was found to be the main compound. Conclusion: The integration of simplex centroid model and quantification by HPLC‐MS/MS is promising. Statistical optimisation of the alkaloid extraction and application of selective, sensitive and robust HPLC–MS/MS method will contribute to quality control applications in phytotherapeutic medicines. Abstract : Since alkaloid drugs is a billionaire market, the investigations on new sources are fundamental to supply an increasing market. To evaluate the effect of the combination of different solvents to increase alkaloids extraction, a simplex‐centroid design developed. In addition, the verification of the alkaloids amount was performed through a validated HPLC–MS/MS method. A mathematical model enabled an optimized condition of extraction. The analysis method was applied to proper quantify alkaloids in the leaves of Unonopsis duckei .